Radiocarbon Determinations and the Mesolithic-Neolithic Transition in Southern Italy - Pluciennik, Mark (Journal of Mediterranean Archaeology, 1998)
More than 120 radiocarbon determinations which are relevant to the issue of the Mesolithic-Neolithic transition are now available from southern Italy. Previous treatments of this topic have tended to concentrate on identifying the earliest Neolithic traits and sites. It is suggested that ideas of the transition are better placed in the context of discussion of the Mesolithic Holocene hunter-gatherers, as well as the introduction of new domesticated crops and animals and material culture which conventionally signify the Neolithic. Radiocarbon determinations from the provinces of Basilicata, Calabria, Campania, Puglia, Sardinia and Sicilia are critically evaluated, and it is noted that for a variety of reasons there is a substantial gap lasting about 1000 calendar years in our knowledge of the latest dated Mesolithic and earliest dated Neolithic in southern Italy. This gap, as well as the academic divide caused by periodization of the archaeological record into Mesolithic and Neolithic, is argued to privilege models which see the Neolithic as necessarily radically different and largely due to social dynamics deriving from outside southern Italy.